IMPLEMENTATION OF SERVICE EXCELLENCE IN HIGHER EDUCATION TO INCREASE STUDENT SATISFACTION AS CUSTOMERS: A CASE STUDY OF A PRIVATE UNIVERSITY IN JAKARTA - Ihin Solihin (Adisam Publisher, 2024)
Every educational institution must of course have quality and qualified Human Resources (HR). Not only the teaching staff or lecturers, but also need to be supported by competent staff/educational staff so that the